INGLIZ VA O‘ZBEK TILIDA KONSENSUM TUSHUNCHASINING LINGVOKOGNITIV VA MILLIY-MADANIY TAHLILI - Qodirova Munisabonu Ibrohimjon qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article analyzes the linguo-cognitive and cultural aspects of the concept of “consensus” in English and Uzbek. It explores the conceptual frameworks formed around the term, the language units associated with it, and how these reflect the worldview, social values, and communicative norms of each culture. The comparative analysis highlights how the idea of social agreement and unity, as expressed by “consensus,” is represented and perceived in both linguistic and cultural contexts.